PERAN KECERDASAN SPIRITUALITAS DAN KECERDASAN EMOSIONAL TERHADAP KEBERMAKNAAN HIDUP PADA SUSTER OSF YANG PURNAKARYA - Yustina Surani; Indriyati Eko Purwaningsih (Universitas Sarjanawiyata Tamansiswa, 2014)
ABSTRACTThe purpose of this research was to predict the contribution of spiritual and emotional intelligence towards the purpose in life of OSF retired nuns. The participants were 39 nuns. This correlation study used purpose in life scale, spiritual intelligence scale, and emotional intelligence scale to collect data. The data was analyzed with partial correlation and linier multiple regression. Spiritual and emotional intelligence was positively related to the purpose in life ( r = 0,406 ; p <0,05).Â The contribution of spiritual and emotional intelligence was 16,4%. It means that other variables such as sex, knowledge, motivation, age, family environment, and other environment contributing 83,6%. The researcher concluded that: First, the purpose in life of retired nuns can be predicted by spiritual and emotional intelligence; Second, spiritual intelligence supports the purpose in life of retired nuns; Third, emotional intelligence supports the purpose in life of retired nuns.Â Keywords: spiritual intelligence, emotional intelligence, purpose in life